2022
DOI: 10.1177/08927057221086833
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of graphene nanoplatelets/hydroxyapatite in PMMA bone cement for characterization and enhanced mechanical properties of biopolymer composites

Abstract: Polymethylmethacrylate (PMMA) in powder form is broadly used as bone cement in orthopedic applications due to its expanded mechanical, physical, and chemical properties. In this study, a hybrid PMMA biopolymer nanocomposite is developed by the supplement of graphene nanoplatelets (GnP) and hydroxyapatite (HA) powders of nano-size with combined loadings ranging from 0.5 to 2.5 weight %. Both materials were applied uniformly to reinforce commercial bone cement made of polymethylmethacrylate. The findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…To overcome these limitations, several ongoing studies are exploring innovative techniques and improved materials to enhance the capabilities of bioceramics. 24,[79][80][81] These endeavors seek to overcome the challenges associated with their mechanical properties, promote enhanced strength and resilience, and ensure compatibility with the natural regeneration processes of bone. 82…”
Section: Bioceramics For Bone Regenerationmentioning
confidence: 99%
“…To overcome these limitations, several ongoing studies are exploring innovative techniques and improved materials to enhance the capabilities of bioceramics. 24,[79][80][81] These endeavors seek to overcome the challenges associated with their mechanical properties, promote enhanced strength and resilience, and ensure compatibility with the natural regeneration processes of bone. 82…”
Section: Bioceramics For Bone Regenerationmentioning
confidence: 99%
“…4 Recent research studies have shown that therapeutic composites, such as phosphocalcic ceramic materials embedded in biodegradable biopolymers, have promised orthopedic uses in bone tissue regeneration. [5][6][7][8] The main advantages of these materials lie in the combination of the rheological and mechanical qualities of the polymer with the biocompatibility, bioactivity, and osteoconductivity of the bioceramic, which enhances bone regrowth. 9,10 In this research study, researchers developed and analysed a biomaterial that would support a bone regeneration mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It is subtle that these biomaterials are classified into organic or inorganic materials, where calcium phosphate (CaP) bioceramics stand for the majority of inorganic scaffolds while natural or synthetic biopolymers form the majority of organic scaffolds. 4 Recent research studies have shown that therapeutic composites, such as phosphocalcic ceramic materials embedded in biodegradable biopolymers, have promised orthopedic uses in bone tissue regeneration 5–8. The main advantages of these materials lie in the combination of the rheological and mechanical qualities of the polymer with the biocompatibility, bioactivity, and osteoconductivity of the bioceramic, which enhances bone regrowth.…”
Section: Introductionmentioning
confidence: 99%
“…UHMWPE/HDPE/MWCNT nanocomposites were found to be less elastic than their blends. In the study of Dubey et al, 24 the effect of Graphene nanoplatelets (GNPs)/hydroxyapatite (HA) in PMMA bone cement is used to produce a biopolymer composite. The amount of each nanofiller applied is between 0 and 0.5 wt.%.…”
Section: Introductionmentioning
confidence: 99%